Perlindungan Hukum Dokter Lokal atas Praktik Dokter Asing dalam Pemenuhan Hak Pasien , Tantangan, Kebijakan, dan Implikasinya dalam Sistem Kesehatan Nasional - Ilman Fathony Martanegara; Rini Irianti Sundari; Chepi Ali Firman Zakaria (Pusat Riset dan Inovasi Nasional, 2025)
This research explores the legal protection of domestic doctors in Indonesia in response to the increasing utilization of foreign doctors (FDs) within the framework of knowledge transfer aimed at improving healthcare services. With the enactment of Law No. 17 of 2023 on Health, the Indonesian government provides space for foreign doctors to practice with simplified licensing procedures, raising legal concerns regarding legal certainty, professional equality, and the rights of patients to clear and honest communication. This study uses normative juridical methods with statutory and conceptual approaches to analyze the legal framework surrounding this issue. The findings show that the implementation of simplified requirements for foreign doctors potentially threatens the professional standing of local doctors and risks violating patient rights. Recommendations include strengthening legal instruments and monitoring mechanisms to ensure that knowledge transfer objectives are met without compromising legal protection and healthcare quality. The legal framework provided by Law No. 17 of 2023 allows foreign doctors to practice with more straightforward licensing processes, but it raises concerns regarding the adequacy of regulatory oversight. Local doctors fear that the simplified procedures for foreign doctors may not guarantee the same level of competency, accountability, and ethical standards. Furthermore, the presence of foreign doctors could lead to a disparity in professional treatment and recognition, undermining the integrity of the medical profession in Indonesia. This study explores how these legal issues intersect with the broader goals of patient protection, ensuring that all medical practitioners, regardless of nationality, adhere to the highest standards of care and ethical conduct. The role of patient rights in this context is critical, as patients must receive clear and honest communication about the qualifications of the doctors treating them, ensuring their right to informed consent is upheld.